1987
DOI: 10.1128/jb.169.9.3891-3897.1987
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-dependent transport of sugars by Fusobacterium nucleatum ATCC 10953

Abstract: Resting cells of Fusobacterium nucleatum 10953 (grown previously in a medium containing glucose) failed to accumulate glucose under aerobic or anaerobic conditions. However, the addition of glutamic acid, lysine, or histidine to anaerobic suspensions of cells caused the immediate and rapid accumulation of glucose. Except for the amino acid-dependent transport of galactose and fructose (the latter being transported at approximately one-third the rate of glucose), no other sugars tested were accumulated by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
2
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 34 publications
5
70
2
1
Order By: Relevance
“…In some Fusobacterium species, however, transport of sugar depends on amino acid fermentation (Glu, Lys, His or Ser) 40,41 , suggesting that they only thrive in the presence of an ample supply of amino acids. Phenolic compounds are produced from fermentation of the aromatic amino acids phenylalanine and tyrosine 39 , which might increase DNA damage in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…In some Fusobacterium species, however, transport of sugar depends on amino acid fermentation (Glu, Lys, His or Ser) 40,41 , suggesting that they only thrive in the presence of an ample supply of amino acids. Phenolic compounds are produced from fermentation of the aromatic amino acids phenylalanine and tyrosine 39 , which might increase DNA damage in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have so far revealed that carbohydrates, as energy sources, are poorly utilized and their Kermentatioii is limited to only a few species such as F. varium (Gharbia & Shah, 19886). Species were shown to assimilate 30-100% of the available glucose in the medium (Gharbia & Shah, 1988), but [14C]glucose incorporation experiments revealed that this is used for the biosynthesis of various cellular components (G harbia & Shah, 1989b) and storage glycopolymers (Robrish et al, 1987). The latter can, however, be metabolized in the absence of other fermentable substrates (Robrish & Thompson, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Fusobacteria are Gram-negative anaerobic rods that are usually described as weakly or asaccharolytic, and most species, including Fusobacterium nucleatum, use amino acids as fermentable energy sources (Robrish et al, 1987 ;Robrish & Thompson, 1990). The products of metabolism (acetic, butyric and propionic acids) may penetrate periodontal tissue, thereby contributing to the aetiology of gingivitis and periodontal disease.…”
Section: Introductionmentioning
confidence: 99%